RETRACTED: PRESERVATION POTENTIAL OF COMBINATION OF CLOVE AND LEMON BASIL ESSENTIAL OILS ON FRESH CHICKEN MEAT - Dwi Hartanti; Nur Annisa Septiyaningrum; Alwani Hamad (Indonesian Association of Food Technologists, 2019)
We found this paper already published in the Journal of Food Quality and Hazards Control 2020: 7 (2): 84-93 with the title